Synthesis, characterization, electrochemistry and spectroelectrochemistry of new non-peripherally hexyl benzoate substituted CoII, CuII , MnIII(Cl) phthalocyanines - Kilicarslan, Fatma A.; Erdogmus, Ali; Bilgen, Elif; Koca, Atif (ELSEVIER SCIENCE SA, 2025)
Metallo phthalocyanines (MPcs) non-peripherally substituted with hexyl benzoate and bearing Co2+, Cu2+, Mn3+(Cl) metal centers, which are labeled as CuPc, CoPc, and MnPc respectively, were synthesized and then characterized with mass, UV-Vis, and FT-IR spectroscopy techniques. Then, the spectroelectrochemical and electrochemical characterizations of these complexes were carried out. The voltametric and spectroelectrochemical responses indicated that while phthalocyanine (Pc) bearing Cu2+ (CuPc) illustrated only Pc-based electron transfer processes, metal-based redox reactions were observed for the CoPc and MnPc in addition to the Pc ring-based ones. While CoPc illustrated one metal based oxidation and one metal based reduction processes in addition to the phthalocyanine ring based electron transfer reactions, MnPc illustrated two metal based reductions and phthalocyanine ring based electron transfer reactions. Altering the solvent of the electrolyte (dimethyl sulfoxide and dichloromethane) influenced the redox characters of all complexes due to the coordination/noncoordinating of the solvents of the electrolyte to the metal center of the complexes, and coordination of the donor solvent dimethyl sulfoxide solvent to the metal center stabilized the high oxidation state of the cobalt center of CoPc. Electron transfer reactions of the complexes significantly influenced their spectral responses; thus, predominant spectral and color changes were observed during the spectroelectrochemical measurements.
Keywords: Cupper (II) phthalocyanine; Cobalt (II) phthalocyanine; Manganese (III) phthalocyanine; Electrochemistry; Spectroelectrochemistry; HOLE-TRANSPORTING MATERIALS; PEROVSKITE SOLAR-CELLS; MANGANESE PHTHALOCYANINE; DOPANT-FREE; COBALT; METAL; EFFICIENT; PERFORMANCE; COMPLEXES; CO(II); Chemistry